THE IMPACT OF TAX AVOIDANCE, PROFITABILITY, LEVERAGE, AND COMPANY SIZE ON EARNINGS MANAGEMENT - Kusuma, Yasa Mulya; Lukman, Hendro (International Journal of Application on Economics and Business, 2023)
Companies doing earnings management have different goals or can be caused by several factors. several factors that can cause management to carry out earnings management include profit, leverage, company size, tax avoidance and others. This study aims to obtain empirical evidence and analysis of the influence of these factors on earnings management in non-cyclical consumer goods companies listed on the Indonesia Stock Exchange for the 2015-2020 period. Sampling using purposive sampling method. The number of data samples studied were 173 data from 31 companies. The analysis of this research is multiple linear regression analysis. The results of this study indicate that tax avoidance has an effect on earnings management, while other variables, profitability, leverage, and firm size have no effect on earnings management. The implication of this research is that the government must continue to close loop-wholes in tax laws and regulations to minimize earnings management practices